2022
DOI: 10.1038/s41598-022-16730-1
|View full text |Cite
|
Sign up to set email alerts
|

During the COVID-19 pandemic participants prefer settings with a face mask, no interaction and at a closer distance

Abstract: Peripersonal space is the space surrounding our body, where multisensory integration of stimuli and action execution take place. The size of peripersonal space is flexible and subject to change by various personal and situational factors. The dynamic representation of our peripersonal space modulates our spatial behaviors towards other individuals. During the COVID-19 pandemic, this spatial behavior was modified by two further factors: social distancing and wearing a face mask. Evidence from offline and online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Moreover, participants who reported overall greater physical isolation, stronger feelings of social closeness and higher perceived threat of COVID-19 gave more positive ratings to images depicting individuals alone and in very small groups. Our findings are also in line with Kühne et al (2022), who found that following the pandemic, participants perceived situations in which two individuals were depicted wearing face masks and not interacting with one another as more positive. One important and surprising insight emerging from the current study is that COVID-19 has had an impact on human perception of social touch, such that observing nonsocial touch evoked more positive emotions than observing human touch.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, participants who reported overall greater physical isolation, stronger feelings of social closeness and higher perceived threat of COVID-19 gave more positive ratings to images depicting individuals alone and in very small groups. Our findings are also in line with Kühne et al (2022), who found that following the pandemic, participants perceived situations in which two individuals were depicted wearing face masks and not interacting with one another as more positive. One important and surprising insight emerging from the current study is that COVID-19 has had an impact on human perception of social touch, such that observing nonsocial touch evoked more positive emotions than observing human touch.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, faces wearing face masks may have been a sign of health [ 14 ], and the degree of familiarity may have been equal between the unoccluded and faces wearing face masks [ 19 , 21 , 55 ]. In any case, face masks are nowadays becoming a social tool [ 56 ]. Notably, however, the significant simple-simple main effect of time point was only for LAFs wearing face masks.…”
Section: Discussionmentioning
confidence: 99%
“…The use of masks has proven to be an effective strategy to slow the spread of COVID-19. Even in a critical situation such as a pandemic, it really helps people to socialize with other people because the mindset of each individual believes that masks can protect themselves from viral infections [12]. However, in indigenous communities in rural areas, these preventive measures tend to give a negative response [22].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, COVID-19 can attack various ages and genders, this greatly affects the psychology of society because of the fear of being exposed to COVID-19 [2][3][4]. The risk of contracting COVID-19 can cause death, therefore people are vigilant by vaccinating [5][6][7] and use masks on individuals as a form of self-protection from the virus [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%